KOMUNIKASI DAN NOMINASI BAKAL CALON KEPALA DAERAH POPULAR NIRELEKTABILITAS - Taufik, Cevi Mochamad; Aditya, Krisna; Suhaeri, Suhaeri (KOMUNIKA BANGSA, 2024)
The popularity of celebrities is quantified as capital for political parties to win the competition in the regional election contestation simultaneously in November 2024. The method which later became a model for political parties to win the contest continues to be reproduced every time before the political event. Popularity is considered to be able to increase profitable opportunities amidst public ignorance of politicians or regional head candidates. The emergence of celebrities on the political scene is nominated to increase popularity without considering their ability to lead and solve social problems currently facing society. In consideration of political parties only victory. Other calculations regarding electability can be resolved through the massification of information via social media about prospective candidates. Based on this background, the aim of the research is to understand the popularity and victory of political parties in regional election contestations. The method used is media content analysis with a qualitative approach. This aims to understand the phenomena behind the visible symptoms. The research results show that popularity must be accompanied by electability as a provision for contestation. To develop these two staff, they must communicate intensively both through direct meetings and through communication media.